DAYA SERAP SISWA TERHADAP PEMBELAJARAN TAKSONOMI PENDIDIKAN AGAMA ISLAM - Fauzi, Ahmad (LPPI Universitas Al-Qolam Malang, 2017)
Each person's physical and spiritual growth and development differ from one to another. This will affect the absorption of students in obtaining material or absorbing education materials. In the context of the taxonomy of learning it also affects. This article describes the taxonomy of learning has been conceived by Bloom. It also explores how those kinds of learning taxonomies should be utilized to maximize the acquisition of teaching and learning, so that education activities is not only improve one kind of potency but all of three kinds of the taxonomy. Keywords: Absorption, Taxonomy, Learning